Willingness to Communicate and Second Language Proficiency: A Correlational Study - Pornapit Darasawang; Hayo Reinders (MDPI AG, 2021)
This study attempts to answer one straightforward question: "what is the relationship between students' proficiency level and their willingness to communicate?", i.e., their "readiness to enter into discourse at a particular time with a specific person or persons", using an L2. Understanding the link between proficiency and WTC is important as a great deal of effort is expended by teachers worldwide on encouraging learners to engage in L2, interaction more. If their willingness to do so depends (in part) on their proficiency level at the time, this may affect what type of activities and instruction are to be provided in class, especially compulsory English classes where students have less autonomy and motivation. To establish this relationship, we correlated 1836 Thai university students' English Placement Test scores with their level of WTC as measured through a three-part survey instrument, with WTC operationalised as "self-perceived willingness to communicate", "communicative self-confidence", and "self-perceived L2 use". We found a weak to moderate correlation between WTC and language proficiency, with the construct of "self-confidence" being the most strongly correlated. We discuss some of the implications of these findings in relation to EFL teaching.